Preliminary data on slow-moving landslides-affected urban areas through geological, geomorphological and insar analysis - Cianflone, Giuseppe; Conforti, Massimo; Soleri, Sergio; Ietti, Fabio (Italian journal of engineering geology and environment, 2021)
<span data-sheets-value=""1":2,"2":"The research focuses on the instability phenomena occurring on the eastern edge of the Calabria oastal Range using geological and geomorphological investigations, geognostic surveys and InSAR remote sensing technique. The study area is located in Cosenza province (Calabria, south Italy) and includes Cavallerizzo, Cerzeto, San Martino di Finita and Rota Greca villages. The geological setting is dominated by a variety of metamorphic-crystalline rocks constituting the Coastal Range structure. A normal fault, N-S oriented and located on the eastern side of the Costal Range, is responsible of the tectonic contact between the metamorphic rocks and the sedimentary deposits of the Crati Basin; while, a colluvial deposit overlies both the crystalline and the Neogene terrains. Continuous boreholes showed that the thickness of this deposit ranges from 10 to 65 m. The latter is involved in widespread landslides causing severe harmful to buildings and infrastructures. Envisat ascending dataset, processed by SBAS multi-temporal InSAR technique, was employed to measure the displacement time series referred to the interval 2003-2010. The data acquired along Envisat ascending orbit, which better cover the east-facing study area, showed a ground movement rate up to -6.5 mm/yr for the landslides in the urbanized areas; whereas, ERS descending orbit (ascending data are not available) showed movement rate of 7.5 mm/yr."" data-sheets-userformat=""2":13057,"3":"1":0,"11":0,"12":0,"15":"Arial","16":10">The research focuses on the instability phenomena occurring on the eastern edge of the Calabria oastal Range using geological and geomorphological investigations, geognostic surveys and InSAR remote sensing technique. The study area is located in Cosenza province (Calabria, south Italy) and includes Cavallerizzo, Cerzeto, San Martino di Finita and Rota Greca villages. The geological setting is dominated by a variety of metamorphic-crystalline rocks constituting the Coastal Range structure. A normal fault, N-S oriented and located on the eastern side of the Costal Range, is responsible of the tectonic contact between the metamorphic rocks and the sedimentary deposits of the Crati Basin; while, a colluvial deposit overlies both the crystalline and the Neogene terrains. Continuous boreholes showed that the thickness of this deposit ranges from 10 to 65 m. The latter is involved in widespread landslides causing severe harmful to buildings and infrastructures. Envisat ascending dataset, processed by SBAS multi-temporal InSAR technique, was employed to measure the displacement time series referred to the interval 2003-2010. The data acquired along Envisat ascending orbit, which better cover the east-facing study area, showed a ground movement rate up to -6.5 mm/yr for the landslides in the urbanized areas; whereas, ERS descending orbit (ascending data are not available) showed movement rate of 7.5 mm/yr.